Social axioms: A new culture measure for South African business research - S. M. Burgess (South African Journal of Business Management, 2011)
This study is intended to introduce social axiom theory to South African business researchers and, in this process, to provide new empirical evidence pertinent to the South African context. We examine social axioms in the largest and most representative national metropolitan population ever studied, providing scores for social axiom dimensions at the individual-level and nation-level, as well as assessments of relations with sociodemographics, values, personality and life satisfaction. The results support the convergent validity, discriminant validity and composite reliability of the 25-item brief version of the Social Axioms Scale. We extend prior research on social axioms and personality by examining relations with optimum stimulation level (OSL), an important personality construct studied in marketing and human resource management. A hierarchical regression model illustrates the power of social axioms in predicting life satisfaction, over and above the effects of sociodemographics, values and optimum stimulation level. Several points of departure for fruitful business research are identified.
Keywords: 650